Efektifitas Model Aida Sebagai Strategi Pemasaran Dan E-Wom Untuk Mempengaruhi Minat Beli Konsumen Di Era Digital: (Studi Kasus Pada Produk Hanasui) - Mulyati, Hana Putriana; Sudrajat, Ajat (Politeknik Negeri Ambon, 2024)
Creativity in creating advertisements that will be posted on social media is considered important to attract the attention of the audience in looking for more information about the product, so that the audience wants to purchase the product. The aim of this research is to determine the level of effectiveness of the AIDA model as a marketing and e-WOM strategy to influence consumer buying interest in the digital era. This research uses a quantitative approach with a questionnaire as a research instrument. Researchers distributed questionnaires to Hanasui product users. The primary data obtained was then analyzed using the SEM-PLS method using the Smart-Pls 4.0 software. Based on the tests that have been carried out, the results obtained show that the AIDA and e-WOM models have a positive and significant effect on consumer buying interest in the digital era. The AIDA model as Hanasui's digital marketing strategy has also been effective in building consumer interest and interest in making purchases. Â Keywords: AIDA Model;Â e-WOM; Â interest buying